2011
DOI: 10.1136/jmg.2010.083345
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of genetic variants in hypertrophic cardiomyopathy by custom DNA resequencing array in clinical practice

Abstract: Although next-generation sequencing will replace all large-scale sequencing platforms for inherited cardiac disorders in the near future, this HCM resequencing array is currently the most rapid, cost-effective and reasonably efficient technology for first-tier mutation screening of HCM in clinical practice. Because of its design, the array is also an appropriate tool for initial screening of other inherited forms of cardiomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 29 publications
2
28
1
4
Order By: Relevance
“…Approximately 33 samples were necessary to attain the maximum call-rate in GSEQ. A similar observation was described previously (Fokstuen et al 2011). No-call regions are one of the problems of ResAT.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Approximately 33 samples were necessary to attain the maximum call-rate in GSEQ. A similar observation was described previously (Fokstuen et al 2011). No-call regions are one of the problems of ResAT.…”
Section: Discussionsupporting
confidence: 69%
“…This technology has been used for multiple-gene analysis in childhood hearing loss (Kothiyal et al 2010), breast-ovarian cancer syndrome (Schroeder et al 2010), dilated cardiomyopathy (Zimmerman et al 2010), X-linked intellectual disability (Jensen et al 2011), familial hypercholesterolemia (Chiou et al 2011), and hypertrophic cardiomyopathy (Fokstuen et al 2011). DiVerent research groups have shown ResAT to be a highly eYcient, relatively accurate, cost-eVective, and rapid method.…”
Section: Introductionmentioning
confidence: 99%
“…These variants have previously been associated with cardiomyopathy [18][19][20] a clinical feature not detected in our two patients. A similar scenario occurs for the nonsense c.4363G > T/p.Glu1455*, already reported elsewhere [21].…”
Section: Previously Described Mutationsmentioning
confidence: 77%
“…Fig. 1), pediatric interventions, and cerebrovascular applications [39] as potential beneficial indications for DCB catheters. In the coronary application, DCB are not a replacement for DES.…”
Section: > a Promising Alternative To Stand-alone Balloon Angioplastymentioning
confidence: 99%